Beethoven Hero - Burnham, Scott G. (Book collections on Project MUSE., 1995)
In addition to thus identifying Beethoven's music as an overarching expression of values central to the age of both Goethe and Hegel, the author describes and then critiques the process by which the musical values of the heroic style quickly became the controlling model of compositional logic in Western music criticism and analysis. Apart from its importance for students of Beethoven and his music, this book should appeal to all those interested in canon formation in the arts and in music as a cultural, ethical, and emotional force - in short, to anyone interested in the questions of what we want from music and what music does for us.